P58 Setting up an encephalitis multidisciplinary meeting in a tertiary neurology centre - Bharucha, T; Brown, R; Bamford, A; Kaliakatsos, M; Hoskote, C; Breuer, J; Manji, H; Zandi, M (Journal of neurology, neurosurgery and psychiatry, 2019)
ObjectivesTo improve the outcome of encephalitis in the region.DesignService evaluation of the introduction of monthly encephalitis meetings attended by specialist neuroradiologists, neurologists and infection doctors.SubjectsPatient referred at the discretion of the clinician from local hospitals and the tertiary referral centre.MethodsDiagnosis confirmed at the MDT or as a direct result of the MDT discussion.ResultsTo be presented.ConclusionsEncephalitis is a rare and complex clinical syndrome that requires close communication between neurologists and infection doctors. Setting up an MDT established this interaction, and streamlines patient care. Further, it provides access to novel technologies such as metagenomic diagnostic approaches.